Beyond Vulnerability? Turkey and the 1970 Kurdish Autonomy Deal in Iraq - SEVER, AYŞEGÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
The article aims to explore internal and external conditions that unprecedently determined Turkey's low profile response to the most advanced Kurdish autonomy agreement between Baghdad and Barzani on 11 March, 1970. Despite Ankara's complete denial of the Kurdish presence in its own territory and thereby its vulnerability to the transborder Kurdish developments, the Turkish government unprecedently reacted calmly and gave the cold shoulder to the agreement. Was this a disguised reaction or an expression of the real Turkish considerations about the Kurdish-Iraqi deal? In order to comprehend the reasons behind the restrained Turkish reaction to the agreement, several elements are to be explored simultaneously. Taking the multiple causes of the Turkish response into account, the article will shed light on a little-explored issue, the Turkish policy towards the transborder Kurdish developments in the Cold war. Furthermore, it will provide relevant historical background to comprehend Turkey's present relations with the Kurds of the Middle East in the context of increasing internationalization of the Kurdish issue.
Keywords: Kurdish politics; Turkish politics; Barzani; Middle East; Ethnic politics; POLICY